Otherness and Alienation in Jana Egle’s Fiction - Romanovska, Alina (Respectus Philologicus, 2024)
The Latvian writer and poet Jana Egle devotes special attention in her texts to people who are perceived by society as “others”. Such individuals are frequently regarded as anomalous by those in their immediate vicinity, which often results in a sense of detachment and disconnection. In her short fiction, Egle examines a range of forms of otherness, including individuals from diverse national backgrounds, members of the LGBTQ+ community, and those facing social disadvantage. Adults are frequently influenced by long-standing stereotypes and traumatic experiences, whereas children tend to be more receptive to forming close relationships due to the absence of such biases. This article seeks to examine the manifestations of otherness in Egle’s works through the lens of the self-other binary and the insights gleaned from contemporary researchers on identity issues. Egle adroitly depicts the tenuous and nebulous border between the self and the other by exploring the inner realms and experiences of the marginalised. Through catharsis, she fosters a sense of proximity between these “others” and the reader. Despite portraying tragic scenarios, she maintains a quality of levity that is challenging to articulate but perceptible.
Keywords: self-other binary; otherness; alienation; identity; Jana Egle; contemporary Latvian literature